Spain : Financial Sector Assessment Program-Technical Note-Institutional Arrangements for Financial Sector Oversight. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Spain regarding institutional arrangements for financial sector oversight. The macroprudential policy framework for banking is now in place, although the national macroprudential authority has not been established. Banco de Espana is the national designated authority for exercising certain macroprudential powers and, under the Banking Union, shares macroprudential oversight with the European Central Bank, which possesses 'top-up' powers. It is recommended that the macroprudential toolkit be expanded, particularly to include more effective tools to deal with risks associated with real estate exposures. Monitoring of system-wide trends also needs to be conducted with a greater focus on risks and macro-financial perspectives.